Estratégias para o desenvolvimento de produtos contra o desgaste dentário erosivo por meio da engenharia de película adquirida com CaneCPI-5: translação das ciências básicas para a clínica - Pelá, Vinicius Taioqui (Universidade Federal de São Carlos, 2022)
Currently, the scientific development of sugarcane-derived cystatin (CaneCPI-5) has gained strength in the control of erosive tooth wear (ETW). However, for this recombinant protein to be commercially used, it is important to verify the strategies related to its use, as well as including its translation from basic sciences to clinical application, in order to direct the development of new dental products to protect against ETW. Thus, the objective of the present thesis was to evaluate the protective effect of CaneCPI-5 in different acquired pellicle engineering protocols (in vitro, in situ and in vivo), as well as to test it in different combinations and application vehicles against ETW. In order to achieve this objective, seven experimental chapters were carried out, which are described below. In the first chapter, an in vitro acquired enamel pellicle (AEP) formation and collection protocol for proteomic analysis was developed. In the second chapter, the difference in the protein profile of the AEP was demonstrated when the in vitro, in situ and in vivo conditions were compared. The third chapter was intended to understand the mechanism of action of CaneCPI-5 and other treatments (alone or combined) in the presence or absence of acquired pellicle on native enamel specimens, using an in vitro dental erosion protocol. Subsequently, the fourth chapter showed that the combination of CaneCPI-5 with an inorganic component (sodium fluoride) favored enamel protection against initial dental erosion in vitro. The fifth chapter was designed primarily to ensure that CaneCPI-5 was safe for gingival fibroblast cells through in vitro cytotoxicity assays. In addition, in this chapter there was a clinical advance in the use of CaneCPI-5 (in solution form), through an in situ protocol, which demonstrated that this protein has a protective effect against more severe wear, involving erosion and erosion associated with abrasion. Subsequently, the sixth chapter also demonstrated the effectiveness of CaneCPI-5 when it was incorporated into a different application vehicle (chitosan gel) for the prevention of erosion and erosion associated with in situ abrasion. Finally, in the last chapter (seventh), it was demonstrated a real clinical interpretation of the protective effect of a mouthrinse with CaneCPI-5 and the use of the Reflectometer Optipen for the analysis of initial dental erosion in vivo. In conclusion, the present thesis demonstrated several innovative strategies on the use of CaneCPI-5 against enamel ETW. These results favor the design of new dental products.
Strategies for the development of products against erosive tooth wear through the acquired pellicle engineering with CaneCPI-5: translation of basic sciences to the clinic
Keywords: Canacistatina; Erosão dentária; Saliva; Proteção; Película adquirida; Acquired pellicle; Canacystatin; Dental erosion; Protection; Saliva; CIENCIAS DA SAUDE::ODONTOLOGIA::ODONTOLOGIA SOCIAL E PREVENTIVA